Glasses for photonics - Yamane, Masayuki (Cambridge University Press, 2000)
"This book is an introduction to recent progress in the development and application of glass with special photonics properties." "Fundamentals of glass materials are explained in the first chapter and the book then proceeds to a discussion of gradient index glass, laser glasses, nonlinear optical glasses and magneto-optical glasses. Beginning with the basic theory, the book discusses actual problems, performance and applications of glasses. The authors include much useful background material describing developments over the past 20 years in this rapidly moving field."